Reduced vertebrate diversity independent of spatial scale following feral swine invasions. Issue 13 (14th June 2019) - Ivey, Matthew R.; Colvin, Michael; Strickland, Bronson K.; Lashley, Marcus A.
Abstract: Biological invasions often have contrasting consequences with reports of invasions decreasing diversity at small scales and facilitating diversity at large scales. Thus, previous literature has concluded that invasions have a fundamental spatial scale‐dependent relationship with diversity. Whether the scale‐dependent effects apply to vertebrate invaders is questionable because studies consistently report that vertebrate invasions produce different outcomes than plant or invertebrate invasions. Namely, vertebrate invasions generally have a larger effect size on species richness and vertebrate invaders commonly cause extinction, whereas extinctions are rare following invertebrate or plant invasions. In an agroecosystem invaded by a non‐native ungulate (i.e., feral swine, Sus scrofa ), we monitored species richness of native vertebrates in forest fragments ranging across four orders of magnitude in area. We tested three predictions of the scale‐dependence hypothesis: (a) Vertebrate species richness would positively increase with area, (b) the species richness y‐intercept would be lower when invaded, and (c) the rate of native species accumulation with area would be steeper when invaded. Indeed, native vertebrate richness increased with area and the species richness was 26% lower than should be expected when the invasive ungulate was present. However, there was no evidence that the relationship was scale dependent. Our data indicate the scale‐dependent effect of biological invasions may not apply to vertebrate invasions. Abstract : Previous research claims effects of biological invasions are scale‐dependent across taxa of invader. Forest fragments of varying size, both invaded and non‐invaded by a feral swine, were monitored to determine relationships with native vertebrate species richness. Native vertebrate species richness increased with patch area and was 26% lower than expected when feral swine were present, but that relationship was independent of scale.